Direct Oral Anticoagulants in Cardioversion: A Review of Current Evidence. Issue 3 (March 2018) - Gibson, Caitlin M.; Basto, Amanda N.; Howard, Meredith L.
Objective: Direct oral anticoagulants (DOACs) are recommended for the prevention of stroke or systemic embolism in nonvalvular atrial fibrillation. Dabigatran, rivaroxaban, apixaban, and edoxaban represent possible alternatives to warfarin in the setting of cardioversion. A literature review was conducted to evaluate the safety and efficacy of DOAC use pericardioversion.Data Sources: A PubMed and MEDLINE search through August 2017 was conducted using the following search terms alone or in various combinations: dabigatran, rivaroxaban, apixaban, edoxaban, betrixaban, DOAC, NOAC, TSOAC, cardioversion .Study Selection and Data Extraction: All English-language, human studies comparing the safety and efficacy of DOACs with that of other anticoagulants in the setting of cardioversion were eligible for inclusion. References from published articles were reviewed for additional relevant citations for study inclusion. Four retrospective and 2 prospective trials comparing DOACs with warfarin were identified.Data Synthesis: The majority of studies included patients undergoing electric cardioversion. Based on current evidence, the DOACs perform similarly to warfarin in the prevention of stroke and systemic embolism, and bleeding rates are comparable.Conclusions: DOACs may be an attractive alternative to warfarin because of fast onset of action, potentially reducing delay to cardioversion. More robust studies are needed in patients with renal dysfunction and patients undergoing pharmacological cardioversion.